Growth, Development and Productivity of Shade Varieties in Medium Salt Soils - Yigitaliyev Dilmurod Tolqin o‘g‘li; Ibragimov Baxodir Yusupaliyevich (International Journal on Orange Technologies, 2021)
Harmful salts in the soil, which are soluble in water, adversely affect the growth and development of plants. As a result, there is a sharp decline in productivity. With this in mind, the authors are conducting research on agro technologies for growing different shade varieties in wheat-free areas under moderately saline soils.